Ag containing polydopamine coating on a melt-derived bioactive glass-ceramic: Effect on surface reactivity. Issue 13 (September 2018) - Tejido-Rastrilla, R.; Baldi, G.; Boccaccini, A.R.
Abstract: We have synthesized a silicate bioactive glass-ceramic (BGC1) in the system SiO2 -CaO-Na2 O-P2 O5 -K2 O-MgO-CaF2 which was used to fabricate pellets by powder compaction and sintering. The surface of BGC1 pellets was coated with polydopamine by using a simple immersion method. Silver nanoparticles were then deposited onto the surface of polydopamine modified pellets in order to confer antibacterial properties. The biomineralization ability was tested by soaking the samples in simulated body fluid (SBF). Results showed the successful deposition of both polydopamine and silver nanoparticles on the bioactive glass-ceramic surface. In addition, the formation of a hydroxyapatite layer (HA) on the surface of the samples after soaking them in SBF was confirmed. The kinetics of HA formation was minimally reduced by the presence of polydopamine. Highlights: Polydopamine was deposited onto the surface of glass-ceramic pellets. The presence of polydopamine and silver particles was confirmed by SEM and Raman spectroscopy. Samples remain bioactive despite the presence of polydopamine or silver particles.